2018
DOI: 10.2174/1389203719666180608091849
|View full text |Cite
|
Sign up to set email alerts
|

Disorder in Milk Proteins: Lactadherin Multifunctionality and Structure

Abstract: Milk fat globule membrane (MFGM) is one of the milk components that is produced by the lactating mammary glands and released to the milk in the form of vesicles. MFGM surrounds milk fat globule secreted by the milk producing cells and has a complex structure containing various lipids (e.g., triacylglycerides, phospholipids, and cholesterol), proteins and other macromolecules. Among the proteinaceous components of MFGM is lactadherin, also known as milk fat globule-EGF factor 8 protein (MFG-E8). Being one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…We have previously shown that polymicrobial sepsis after acute alcohol exposure is associated with reduced expression of MFG-E8, and can be ameliorated by the administration of rmMFG-E8 (Wu et al 2010), thus revealing a novel potential targeted therapy for sepsis in alcohol abusers. MFG-E8 is a secreted glycoprotein ubiquitously expressed and abundant in milk, including human breast milk (Yasueda et al 2015; Sabha et al 2018). Mainly produced by phagocytes such as macrophages and dendritic cells, MFG-E8 is necessary for their optimal clearance of dying (mostly apoptotic, but also autophagic, necrotic, necroptotic, pyroptotic) cells (Hanayama et al 2002; Aziz et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that polymicrobial sepsis after acute alcohol exposure is associated with reduced expression of MFG-E8, and can be ameliorated by the administration of rmMFG-E8 (Wu et al 2010), thus revealing a novel potential targeted therapy for sepsis in alcohol abusers. MFG-E8 is a secreted glycoprotein ubiquitously expressed and abundant in milk, including human breast milk (Yasueda et al 2015; Sabha et al 2018). Mainly produced by phagocytes such as macrophages and dendritic cells, MFG-E8 is necessary for their optimal clearance of dying (mostly apoptotic, but also autophagic, necrotic, necroptotic, pyroptotic) cells (Hanayama et al 2002; Aziz et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Milk fat globule-epidermal growth factor-factor VIII (MFG-E8), also called lactadherin, is a secreted glycoprotein abundant in milk, including human breast milk (Yasueda et al 2015; Sabha et al 2018). We have shown that, among other functions such as anti-coagulant (Shah et al 2012), anti-atherogenic (Miksa et al 2009b), pro-extracellular matrix remodeling (Aziz et al 2013) and enterotrophic activity (Bhatty et al 2017), MFG-E8 has anti-inflammatory properties (Miksa et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It decreases over time during lactation when the child is developing its immune system (L€ onnerdal 2016). Lactadherin, another glycoprotein found in human milk, known as milk fat globule-epidermal growth factor 8 (MFG-E8) as well, has been shown to have specific anti-viral functions and prevents rotaviral infection in the newborn (Sabha et al 2018). More than that, it prevents intestinal inflammation by enhancing the phagocytosis of apoptotic cells (Aziz et al 2017).…”
Section: Antimicrobial Proteinsmentioning
confidence: 99%
“…More than that, it prevents intestinal inflammation by enhancing the phagocytosis of apoptotic cells (Aziz et al 2017). In addition, a recent study showed that lactadherin can prevent necrotizing enterocolitis (NEC) by enhancing intestinal barrier integrity (Sabha et al 2018). Milk fat globules (MFGs) are milk lipids present in the form of dispersed droplets (Martini, Salari, and Altomonte 2016).…”
Section: Antimicrobial Proteinsmentioning
confidence: 99%